The effect of metal ions on Staphylococcus aureus revealed by biochemical and mass spectrometric analyses - Chudobova, Dagmar; Dostalova, Simona; Ruttkay-Nedecky, Branislav; Guran, Roman; Rodrigo, Miguel Angel Merlos; Tmejova, Katerina; Krizkova, Sona; Zitka, Ondrej; Adam, Vojtech; Kizek, Rene (Microbiological research, 2015)
In this study, we focused on the effect of heavy metal ions in resistant strains of gram-positive bacteria Staphylococcus aureus using biochemical methods and mass spectrometry. Five nitrate solutions of heavy metals (Ag(+), Cu(2+), Cd(2+), Zn(2+) and Pb(2+)) were used to create S. aureus resistant strains. Biochemical changes of resistant strains in comparison with the non-resistant control strain of S. aureus were observed by microbiological (measuring - growth curves and inhibition zones) and spectrophotometric methods (antioxidant activity and alaninaminotransferase, aspartateaminotransferase, alkaline phosphatase, γ-glutamyltransferase activities). Mass spectrometry was employed for the qualitative analysis of the samples (changes in S. aureus protein composition) and for the identification of the strains database MALDI Biotyper was employed. Alterations, in terms of biochemical properties and protein composition, were observed in resistant strains compared to non-resistant control strain. Our results describe the possible option for the analysis of S. aureus resistant strains and may thus serve as a support for monitoring of changes in genetic information caused by the forming of resistance to heavy metals.
Keywords: RNA, Ribosomal; metalothionein; metabolomika; Staphylococcus aureus; RNA ribozomální; Mass Spectrometry; Ions; Metallothionein; Metabolomics; mikrobiální viabilita; hmotnostní spektrometrie; metabolom; Mass spectrometry; Metabolome; kovy; Heavy metals; Resistance; S. aureus; Microbial Viability; spektrometrie hmotnostní - ionizace laserem za účasti matrice; ionty; Metals; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization